Changes to women's childbirth plans during the COVID-19 pandemic and posttraumatic stress symptoms: a cross-national study - Mesquita, Ana; Costa, Raquel; Dikmen-Yildiz, Pelin; Faria, Susana; Silvestrini, Gabriela; Mateus, Vera; Vousoura, Eleni; Wilson, Claire A; Felice, Ethel; Ajaz, Erilda; Hadjigeorgiou, Eleni; Hancheva, Camellia; et al. (My University, 2024)
A considerable number of women giving birth during COVID-19 pandemic reported being concerned about changes to their childbirth plans and experiences due to imposed restrictions. Research prior to the pandemic suggests that women may be more at risk of post-traumatic stress symptoms (PTSS) due to unmet expectations of their childbirth plans. Therefore, this study aimed to examine if the mismatch between women's planned birth and actual birth experiences during COVID-19 was associated with women's postpartum PTSS. Women in the postpartum period (up to 6 months after birth) across 11 countries reported on childbirth experiences, mental health, COVID-19-related factors, and PTSS (PTSD checklist DSM-5 version) using self-report questionnaires (ClinicalTrials.gov: NCT04595123). More than half (64%) of the 3532 postpartum women included in the analysis reported changes to their childbirth plans. All changes were significantly associated with PTSS scores. Participants with one and two changes to their childbirth plans had a 12% and 38% increase, respectively, in PTSS scores compared to those with no changes (Exp(β) = 1.12; 95% CI [1.06-1.19]; p < 0.001 and Exp(β) = 1.38; 95% CI [1.29-1.48]; p < 0.001). In addition, the effect of having one change in the childbirth plan on PTSS scores was stronger in primigravida than in multigravida (Exp(β) = 0.86; 95% CI [0.77-0.97]; p = 0.014). Changes to women's childbirth plans during the COVID-19 pandemic were common and associated with women's postpartum PTSS score. Developing health policies that protect women from the negative consequences of unexpected or unintended birth experiences is important for perinatal mental health.
Keywords: Birth; Childbirth plan; Mental health; Postpartum; Posttraumatic stress disorder